2019
DOI: 10.1051/cocv/2018002
|View full text |Cite
|
Sign up to set email alerts
|

On the codimension of the abnormal set in step two Carnot groups

Abstract: Abstract. In this article we prove that the codimension of the abnormal set of the endpoint map for certain classes of Carnot groups of step 2 is at least three. Our result applies to all step 2 Carnot groups of dimension up to 7 and is a generalisation of a previous analogous result for step 2 free nilpotent groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…
We study the Sard problem for the endpoint map in some well-known classes of Carnot groups. Our first main result deals with step 2 Carnot groups, where we provide lower bounds (depending only on the algebra of the group) on the codimension of the abnormal set; it turns out that our bound is always at least 3, which improves the result proved in [12] and settles a question emerged in [15]. In our second main result we characterize the abnormal set in filiform groups and show that it is either a horizontal line, or a 3-dimensional algebraic variety.
…”
supporting
confidence: 63%
See 2 more Smart Citations
“…
We study the Sard problem for the endpoint map in some well-known classes of Carnot groups. Our first main result deals with step 2 Carnot groups, where we provide lower bounds (depending only on the algebra of the group) on the codimension of the abnormal set; it turns out that our bound is always at least 3, which improves the result proved in [12] and settles a question emerged in [15]. In our second main result we characterize the abnormal set in filiform groups and show that it is either a horizontal line, or a 3-dimensional algebraic variety.
…”
supporting
confidence: 63%
“…the set of critical values of the endpoint map, is negligible or not; we refer to Section 2 for precise definitions. Despite such a simple formulation, only very partial results are known [1,5,6,16,18] even in settings with a rich structure such as Carnot groups [3,7,9,10,11,12,15]. The goal of this note is to provide a contribution in two meaningful classes of Carnot groups: those with nilpotency step 2, and filiform ones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that, in Theorem 3, the bound 1 on the codimension of Abn G can be improved and we conjecture that it holds with a lower bound 3 (see [30] for an analogous open question in step 2 Carnot groups). We are able to prove our conjecture at least when G is the free Carnot group of rank 3 and step 3.…”
Section: Introductionmentioning
confidence: 93%
“…A detailed study of the singular set has been carried out in [13,12] for 3-dimensional analytic sub-Riemannian manifolds with 2-dimensional analytic horizontal distributions: it turns out that such a set has Hausdorff dimension 1 and, actually, it is a semi-analytic curve. Other partial or related results are contained in [34,32,26,27,7,30]. Different approaches to study singular curves are found e.g.…”
Section: Introductionmentioning
confidence: 99%